Blockchain Technology Adoption in Saudi Hospitals: IT Professional Perspectives - Adel KHWAJI; Farookh HUSSAIN; Yaser ALSAHAFI (Communications of International Proceedings, 2020)
While blockchain is an emerging technology that has exponential interest, the literature shows limited real-world examples of blockchain applications that have been applied in developed countries and there is no evidence of its adoption in Middle Eastern hospitals, especially in Saudi Arabia. Before adopting any new technology, it is necessary to know the extent of user acceptance of the technology. This study will investigate the factors that influence the adoption of blockchain technology in Saudi hospitals. The aim of this study is to develop a framework for blockchain decision-making in hospitals to provide a systematic approach to blockchain adoption that takes different perspectives into consideration. The framework developed is based on Technology-Organisation-Environment (TOE) framework and seeks to help healthcare decision-makers by covering three categories of blockchain adoption: technological, organisational and environmental. The implications of this study will contribute to both theory and practice.
Keywords: Blockchain; Adoption; Acceptance; TOE framework.